EVALUASI PERSPEKTIF BALANCED SCORECARD SEBAGAI DASAR PENINGKATAN PENGENDALIAN OPERASIONAL PADA PT. MULTI JAYA NIAGA RAYA - Celine Valencia; Revi Arfamaini (Bajang Institute, 2025)
The company needs to evaluate its operational performance with a high level of accuracy and accountability. The Balanced Scorecard approach measures the performance of each business unit within the company, thereby enhancing operational control by considering the interests of the company through several key perspectives. The constantly evolving market dynamics require companies to innovate in their supply and distribution processes in order to maintain their competitive advantage. This research employs a descriptive qualitative approach to present data in-depth through narrative. Data collection techniques include interviews, observations, and documentation. The primary data sources are both primary and secondary data obtained directly from the company. PT. Multi Jaya Niaga Raya is a Surabaya based company in East Java engaged in the distribution of commercial vehicle and Mitsubishi automotive spare parts. The Balanced Scorecard perspectives examined in this study include financial, customer, internal business process, and learning and growth perspectives. The results of the financial perspective indicate stable profitability, though still suboptimal due to decision-making that is not yet based on financial ratio analysis. In the customer perspective, customer relations are relatively stable; however, market growth is hindered by limited product diversification. The internal business process perspective shows good operational efficiency, but lacks structured work procedures and documentation. The learning and growth perspective indicates high employee productivity, yet it is not balanced with organizational structure and human resource development.